PREVALENCE OF Pasteurella multocida IN BALI CATTLE IN BALI - Besung, I Nengah Kerta; Tono PG, Ketut; Rompis, Aida Louis Tenden; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana; Vol. 8 No. 2 Agustus 2016, 2016)
This study aims to determine the prevalence of Pasteurella multocida in bali cattle in Bali. A total of 300 cows were taken from nasal swabs for isolation and identification of bacteria P . multocida . The samples came from Badung, Denpasar, Gianyar, and Bangli . Samples were grown on blood agar media. Separate colonies were identified by morphology, Gram stain, , Triple sugar Iron Agar, Methyl Red-Voger Proskauer (MRVP), Simmnons Citrate agar, Sulphid Indol Motility, sugars  test and catalase test. Germs that characterizes P . multocida analyzed descriptively. The results showed that as many as 15 samples suffer from P . multocida bacteria spread in Badung 5 cattle (5%) , Denpasar 4  cattle (8%) , Gianyar  4 cattle (8%), and Bangli 2 cattle (2%).
Keywords: Pasteurella multocida, sapi bali, prevalensi, bali cattle, prevalence